An Elderly Gentleman with Acute Lupus Pneumonitis as the Initial Manifestation of Systemic Lupus Erythematosus - Ferrero, Gina; Chernow, Kate; Karpoff, Marissa; Traisak, Pamela; Feinstein, David; Eid, Hala (Case Reports in Rheumatology, 2021)
Systemic lupus erythematosus is a systemic autoimmune disease, with presentations that vary within a population and across the lifespan of an individual. The disease afflicts childbearing women more than men and uncommonly presents in the geriatric population. Lupus pneumonitis is rare, with a reported incidence of 1–4%. Herein, we discuss the case report of an elderly gentleman with biopsy-proven acute lupus pneumonitis (ALP) as an initial presentation of lupus. After starting high-dose steroids, the patient initially improved, though unfortunately endured a non-ST elevation myocardial infarction and recurrent gastrointestinal bleeding. Despite multiple interventions and a prolonged hospital course, his gastrointestinal bleeding persisted. He elected to go on home hospice and ultimately passed away due to ongoing gastrointestinal bleeding. As with our patient, elderly patients can pose a diagnostic dilemma with regard to late-onset lupus; multiple comorbidities and growing evidence that late-onset lupus may manifest with distinct clinical patterns from younger cohorts complicate diagnosis in these patients. It is critical to maintain a broad differential, which includes unusual rheumatic manifestations when management of common comorbidities fails to alleviate symptoms for an elderly patient. Failure to do so may result in delayed diagnosis of rheumatic disease and increased side effects related to treatment. Additionally, this case serves as a reminder that due to the complexity of rheumatic disease and the additional challenge of older patients with baseline comorbidities, sometimes palliative care options may be appropriate.